TORAKOCHIRURGIAPenetrating heart injury – an attempted suicide. Case report - Garbas, Grzegorz; Perdeus, Jakub; Machała, Waldemar (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Stab wounds and gunshots are the most frequent causes of heart injuries. They more rarely are the consequence of fractures of ribs or the breastbone as a condition of imminent danger of life. The authors describe the case of a 61-year old wounded person treated psychiatrically for a long time. This man was admitted to the hospital with a dagger plunged into the left heart chamber. The patient was operated on immediately, making a suture of the muscle of the injured left chamber of the heart. Prolonged pleural drainage was noted in the post-operative course. The patient was discharged in good condition from hospital 23 days postoperatively. He was transferred to the psychiatric unit for further treatment.